Idiopathic Macular Telangiectasia Type 2: The Progressive Vasculopathy. Issue 1 (January 2013) - Engelbert, Michael; Yannuzzi, Lawrence A.
Purpose: To describe the complete sequence of the progressive vasculopathy in macular telangiectasia type 2. Methods: This is a report of a case demonstrating the complete vasogenic sequence in macular telangiectasia type 2 over the course of 15 years, and representative images from a collective of 150 patients with macular telangiectasia type 2 employing fundus photography, fluorescein angiography, and optical coherence tomography. Results: Macular telangiectasia may progress along a predictable vasogenic sequence which consists of nonproliferative stages, characterized by temporal loss of macular luteopigment and inner retinal volume loss in the absence of vascular changes, followed by a progressive proliferative vasculopathy, first involving the deep capillary plexus with eventual extension of the vascular changes circumferentially in the inner retinal capillary plexus. Late proliferative stages may become indistinguishable from advanced neovascular age-related macular degeneration. Conclusions: While it is rare to observe the complete vasogenic sequence of macular telangiectasia type 2, a classification into nonproliferative and proliferative stages can be established, and may prove helpful as the mechanisms driving the pathogenic process through those stages are identified.